Securing Underwater Wireless Communication Networks - Naresh Kumar, D; ., . (International Journal of Engineering and Technology, 2018)
Underwater remote correspondence systems (UWCNs) are especially defenseless against vindictive assaults because of the high piece blunder rates, huge and variable proliferation deferrals, and low data transmission of acoustic channels. The special attributes of the Underwater acoustic correspondence channel and the contrasts between Underwater sensor systems and their ground-based partners require the improvement of productive and solid security instruments. In this class, an entire review of security for UWCNs is exhibited, and the exploration challenge for secure correspondence in this condition is sketched out.UWCNs incorporate sensors and self-ruling Underwater vehicles (AUVs) that collaborate to perform particular applications, for example, Underwater observing. Coordination and data sharing amongst sensors and AUVs make the arrangement of security testing.Â Â Â